Au(i)-mediated N2-elimination from triazaphospholes: a one-pot synthesis of novel N2P2-heterocycles. Issue 2 (10th December 2021) - Yue, Erlin; Dettling, Lea; Sklorz, Julian A. W.; Kaiser, Selina; Weber, Manuela; Müller, Christian
Abstract : N -Sulfonyl-1, 2, 3, 4-triazaphospholes undergo a highly selective and unprecedented transformation to cyclo -1, 3-diphospha(iii )-2, 4-diazane-Au(i ) complexes in the presence of stoichiometric amounts of AuCl·S(CH3 )2 and loss of N2 . Abstract : Novel tosyl- and mesitylsulfonyl-substituted triazaphospholes were synthesized and structurally characterized. In an attempt to prepare the corresponding Au(i )-complexes with stoichiometric amounts of AuCl·S(CH3 )2, cyclo -1, 3-diphospha(iii )-2, 4-diazane-AuCl-complexes were obtained instead. Our here presented results offer a new strategy for preparing such coordination compounds selectively in a one-pot approach.